The right-wing intellectuals and the Argentine University (1955-1983): The right-wing intellectuals and the Argentine University (1955-1983) (Revista de História da UEG (REVHIST), 2021)
In this article, we will discuss the thoughts of seven Argentineans intellectual of right about the University, observing the content of nine books written by these. First, we will provide some data on their biographies, and then we will present what these authors thought about what happened at the Argentine university between 1955 and 1966, about the best model of university to follow, and how they considered what happened at the university during the Peronist government of 1973. We intend to show that these intellectuals combined, equally, the marked anti-communism of the time, with a profound rejection of reformism.Keywords: University. Argentina. Right. Intellectual.